Carcass characteristics and meat quality of growing rabbits fed mango (Mangifera indica) leaf meal as a replacement for wheat offal - Abegunde, V. S.; Azeez, Z. O.; Olawale, P. O.; Lawal, O. A.; Ayeni , J. A.; Saka, A. A.; Ajibulu, J. O.; Haruna, M. A; Odunsi, A. A. (ADAN JOURNAL OF AGRICULTURE, 2025)
The increasing demand for animal protein due to population growth has created a pressing need to explore non-conventional feed resources as a sustainable way to protein shortages. Hence, an 8 week trial was conducted to evaluate the potential of mango (Mangifera indica) leaf meal (MLM) as a replacement for wheat offal in the diets of growing rabbits. A total of 18 unsexed, mixed breed rabbits (New Zealand white x Chinchilla), aged between 6-8 weeks with average live weight of 600-800 g were used for this study. These animals were randomly allotted into three dietary treatments; 0, 5, and 10% MLM replaced wheat offal in a completely randomized design. Proximate composition of MLM was determined as well as carcass traits, physico-chemical and sensory indices of the meat of growing rabbits were evaluated. Result revealed that MLM contained 92.17 ± 0.04% dry matter, 9.63 ±0.54% crude protein, 13.26 ± 0.25% crude fibre, 2.05 ± 0.24% ether extract, 49.41 ± 0.91% nitrogen free extract and 2278.06 ± 0.02% metabolisable energy. The inclusion of MLM in the diet did not significantly (P > 0.05) affect the carcass characteristics of growing rabbits except the live weight and head. Rabbits fed dietary 0 (1533.33g) and 5 (1526.67g) % MLM had similar (P>0.05) values but significantly higher than those on 10% MLM (1286.67g). Meat quality attributes were significantly (P < 0.05) influenced by dietary MLM, except for cooking loss and thermal loss. The dry matter (87.43 – 89.35%) and crude protein (22.55-25.98%) content of the meat sample of rabbits fed dietary MLM increased across the dietary treatments as MLM inclusion levels increased. Dietary MLM had no significant (P>0.05) influence on the organoleptic indices of meat except the juiciness. Juiciness of meat from growing rabbits fed dietary mango leaf meal significantly increased across the dietary treatments as MLM inclusion level increased. This study concludes that MLM can be incorporated up to 10 % in the diet of growing rabbits as it enhanced certain meat quality parameters like dry matter, crude protein content and juiciness without adversely affecting most carcass traits or other sensory qualities.